Peningkatan Kapasitas Petugas Peternakan dalam Analisis Potensi Jerami Padi Sebagai Sumber Pakan Sapi Potong - Syamsu, Jasmal Ahmari; Yamin, Abdul Alim; Purwanti, Sri; Fuad AW, Andi Muh.; Amal, Ichlasul (Jurnal Pengabdian UNDIKMA, 2024)
This community service aims to increase the knowledge and capacity of livestock officers in assessing the potential and carrying capacity of rice straw as feed for beef cattle. This community service activity uses a training method with planning, implementation, and evaluation stages. The assessment instruments for this service are pre-test and post-test and are analyzed using the Paired-Samples T-Test. The results of this community service show that the knowledge and capacity of livestock officers in assessing the potential and carrying capacity of rice straw as feed for beef cattle has increased. This is evidenced by the data before the training; the participant’s knowledge score was 35.5, while after the training, it increased to 86.0.